Individual appmach as means of improvement of quality of knowledge of pupils at lessons of music (Pedagogy of Higher and Secondary Education, 2006)
The article studies the modern problems of using of the individual approach at music lessons.
Keywords: individual approach; tndividuulization of training; specific features